2017
DOI: 10.1016/j.nedt.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of service users involved in recruitment for nursing courses: A phenomenological research study

Abstract: The aim of this study was to gain insight into service users' experiences of participating in recruitment for Adult, Mental Health and Child nursing studies at the authors' university; to establish potential motivations behind such participation; and to make suggestions for improved future practice. The involvement of service users in nurse education and recruitment has for some years been required by the Nursing and Midwifery Council, but there is a dearth of publications on the meaning of that involvement to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Our findings about issues during delivery of patients and public involvement are consistent with previous studies [22,23]. It can be assumed that if these issues are not address it may subsequently result in academic staff having low confidence in involving patients/public.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings about issues during delivery of patients and public involvement are consistent with previous studies [22,23]. It can be assumed that if these issues are not address it may subsequently result in academic staff having low confidence in involving patients/public.…”
Section: Discussionsupporting
confidence: 90%
“…Participating was clearly a positive experience for all the service user respondents, who were able to talk about topics or experiences that were important to them, enjoyed the fact that the candidates were genuinely interested in what they had to say, and/or gained satisfaction from contributing to the recruitment process: 'Great to feel like we were helping to support midwifery as a profession, candidates were lovely and personable, nice to tell our story and share our experiences!' Service users' sharing of stories has been identified as helping them come to terms with living with compromised health (Stevens et al 2017). Similarly the re-telling of birth and care stories by our service users appeared to trigger a therapeutic release of emotion and help them make sense of what happened to them.…”
Section: What Went Wellmentioning
confidence: 86%
“…Another commented that the marking categories could be made clearer to facilitate this. In their exploration of the meaning to service users of involvement in adult, mental health and children's nursing programmes, Stevens et al (2017) identified the issue of power dynamics when assessing interview candidates' performance. Although being treated as an equal was important to Stevens et al's (2017) participants, they were quick to defer to the judgement of faculty staff.…”
Section: What Went Wellmentioning
confidence: 99%
See 1 more Smart Citation